Coordinated Cyber-Attack Detection Model of Cyber-Physical Power System Based on the Operating State Data Link - Wang, Lei; Xu, Pengcheng; Qu, Zhaoyang; Bo, Xiaoyong; Dong, Yunchang; Zhang, Zhenming; Li, Yang (Frontiers in Energy Research, 2021)
Aiming at the existing coordinated cyber-attack detection method with unbalanced attack samples, high data dimensions and noisy data sets, there are problems of low detection accuracy and efficiency, and poor generalization ability. This paper conducts network coordination from the perspective of cyber and physical data fusion of power Cyber-Physical System(CPS) attack detection, and a data link of cyber-physical coupling state is constructed. Based on this, firstly, a classification method for operating status categories based on PCA-David clustering is proposed to achieve accurate labeling of different operating statuses. Then, the adaptive synthetic sampling algorithm is used to balance the categories that exceed the imbalance threshold. Finally, the loss function is improved according to the feature intensity difference of the attack event, and the integrated classifier is constructed based on the CS_GBDT attack classification algorithm. The simulation results show that this method improves the accuracy, recall, F-Score and other indicators of attack detection.